Dynameric G-quadruplex–dextran hydrogels for cell growth applications. Issue 21 (22nd February 2023) - Sardaru, Monica-Cornelia; Morariu, Simona; Carp, Oana-Elena; Ursu, Elena-Laura; Rotaru, Alexandru; Barboiu, Mihail
Abstract : Hybrid dextran–G-quartet dynamers produces tunable biocompatible three-dimensional thixotropic hydrogels, able to support cell growth. Abstract : Hybrid dextran–G-quartet produces tunable biocompatible three-dimensional thixotropic hydrogels, able to support cell growth.